Effected factors on standard measurement method adoption in construction projects using SEM approach - S. A. Muzafar; Muhamad Azry Khoiry; Mukhtar A. Kassem; Noraini Hamzah; Adafin, Johnson; Anis Rosniza Nizam Akbar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Various factors affect the standard method of measurement adoption in civil construction projects, especially in developing countries such as Malaysia. Hence, this study investigates the relationship between affected factors towards standard adoption using the SEM approach. As a case study, this study focused on quantity surveyors working at a consulting firm in Selangor, Malaysia. This study identifies the effect of standard measuring technique adoption in Malaysian building projects that have a beneficial impact. The factors research model is the first stage in determining the reasons for using the most recent standard measuring technique in civil engineering construction projects and explaining the link between the barrier factors and standard adoption. The information was gathered using a questionnaire survey sent to participants at construction firms that used the standard measurement method. The PLS-SEM approach was used by SmartPLS 3 software to construct and assess a hierarchical model to assess variables and their effects on measuring method adoption. The findings revealed that 17 barrier factor indicators had a significant impact on adopting the standard assessment technique. The coefficient of determination (R2 value) of 0.307 represents the proportion of variance in the dependent variable that one or more predictor variables can explain. Furthermore, the conceptual model’s predictive significance value Q2 is 0.156 greater than zero, indicating that it can predict endogenous latent components. The measured effect size (f2) between the barrier factors (exogenous latent) and the adoption of the model’s standard (endogenous latent) was 0.443, indicating that the developed model had significant explanatory power to represent the relationship among the variables of the factors and the effect on measurement method adoption. There is a need to improve the methods and increase the driver elements described in this study to promote the adoption of standard measurement in construction projects, which impacts the adoption of the standard method of measuring. In the future, researchers can start from this study to compare the situation in Malaysia with developed countries to discover shortcomings and develop a framework for measurement factors that can be applied.